Vaccines to prevent pneumonia and improve child survival - Shabir A Madhi; Orin S Levine; Rana Hajjeh; Osman D Mansoor; Thomas Cherian
For more than 30 years, vaccines have played an important part in pneumonia prevention. Recent advances have created opportunities for further improving child survival through prevention of childhood pneumonia by vaccination. Maximizing routine immunization with pertussis and measles vaccines, coupled with provision of a second opportunity for measles immunization, has rapidly reduced childhood deaths in low-income countries especially in sub-Saharan Africa. Vaccines against the two leading bacterial causes of child pneumonia deaths, Haemophilus influenzae type b (Hib) and Streptococcus pneumoniae (pneumococcus), can further improve child survival by preventing about 1 075 000 child deaths per year. Both Hib and pneumococcal conjugate vaccines have proven safety and effectiveness for prevention of radiologically confirmed pneumonia in children, including in low-income and industrializing countries. Both are recommended by WHO for inclusion in national programmes, and, at sharply tiered prices, these vaccines generally meet international criteria of cost-effectiveness for low-income countries. Vaccines only target selected pneumonia pathogens and are less than 100% effective, so they must be complemented by curative care and other preventative strategies. As part of a comprehensive child survival package, the particular advantages of vaccines include the ability to reach a high proportion of all children, including those who are difficult to reach with curative health services, and the ability to rapidly scale up coverage with new vaccines. In this review, we discuss advances made in optimizing the use of established vaccines and the potential issues related to newer bacterial conjugate vaccines in reducing childhood pneumonia morbidity and mortality.